Pengaruh Pembelajaran Online Terhadap Tingkat Motivasi Belajar Mahasiswa/Mahasiswi FEB Akuntansi UKSW di Masa Pandemi COVID 19 - Katharina Ardian Wolo; Paskah Ika Nugroho (Universitas Pendidikan Ganesha, 2021)
The world nowadays is currently being faced with the outbreak of the COVID 19 virus. This clearly has a significant effect on various fields, especially education. Therefore, it takes motivation to learn as a form of critical attitude in balancing the currently worrisome educational situation. Motivation to learn is an essential factor in the field of education. This research was purposed to see the effect of online learning on the learning motivation of SWCU Accounting FEB students. This study uses a quantitative approach, by distributing questionnaires to accounting FEB students. The samples taken from this study were students of class 2017, 2018, and 2019 with a total of 63 respondents. The analysis technique used in this study is a simple linear regression analysis technique. This research was also conducted by testing the validity and reliability, data normality test, linearity test, hypothesis testing and determinant coefficient. The results showed that the significance value of the hypothesis testing was 0.000 less than 0.005. It means that online learning has a positive effect on the learning motivation of SWCU accounting FEB students. In addition, the value of the determinant coefficient or r square is 0.248, which means that online learning contributes to learning motivation by 0.248 or 24.8% and the rest is influenced by other variables.